2022
DOI: 10.3390/polym14112294
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Experimental Assessment of POFA Concrete Incorporating Waste Tire Rubber Aggregate

Abstract: Several researchers devoted considerable efforts to partially replace natural aggregates in concrete with recycled materials such as recycled tire rubber. However, this often led to a significant reduction in the compressive strength of rubberized concrete due to the weaker interfacial transition zone between the cementitious matrix and rubber particles and the softness of rubber granules. Thereafter, significant research has explored the effects of supplementary cementitious materials such as zeolite, fly ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…In accordance with the 2015 Paris Agreement, global carbon emissions from the cement industry must be reduced by at least 16% by 2030 if the Earth is to remain within the pre-global warming temperatures of 1.5 • C or 2 • C [8,9]. However, with continuous urban land expansion, population growth, and economic development, statistics indicate that global cement production will increase from the current 4.08 billion tonnes to 5 billion tonnes within the next 30 years [10,11]. Furthermore, in accordance with the Global Commission on the Economy and Environment (GCEE), if developing countries increase their infrastructure to the current global average levels, then the construction industry will emit 470 gigatonnes of CO 2 into the atmosphere by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the 2015 Paris Agreement, global carbon emissions from the cement industry must be reduced by at least 16% by 2030 if the Earth is to remain within the pre-global warming temperatures of 1.5 • C or 2 • C [8,9]. However, with continuous urban land expansion, population growth, and economic development, statistics indicate that global cement production will increase from the current 4.08 billion tonnes to 5 billion tonnes within the next 30 years [10,11]. Furthermore, in accordance with the Global Commission on the Economy and Environment (GCEE), if developing countries increase their infrastructure to the current global average levels, then the construction industry will emit 470 gigatonnes of CO 2 into the atmosphere by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed for R 2 rubberized concrete wherein the chloride ion penetration increased from 2122 to 2916 c, and from 1640 to 2584 c, at 28 and 90 days, respectively. Moreover, type R 2 rubberized concrete showed lower chloride ion penetration, compared with type R 1 rubberized concrete in which air was easily trapped by the rough surface of the tire particles [44]. The progressive increase in chloride ion penetration with increasing rubber content may be attributed to the weak bonding between rubber particles and cement paste [57].…”
Section: Rapid Chloride Penetration Test (Rcpt)mentioning
confidence: 95%
“…To reverse this situation, the present study adopted a strategy to utilize TRAs with palm oil fuel ash (POFA) to make some new types of concrete useful for structural applications. POFA has been shown to enhance the strength and durability of concrete when it replaced 20 to 30% of cement [42][43][44][45]. Additionally, reuse of various by-products from agro-industry such as POFA may minimize the hazards of disposing such materials and reduce CO 2 emissions associated with Portland cement manufacturing [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…From the figure 2, it was clearly observed that water absorption values were enhanced as increase the substitution level of waste rubber tyre ash in the concrete mix [42][43][44][45]. The water absorption values of sample SC100, SC95, SC90, SC85 and SC80 were 7.5, 7.7, 8, 8.3 and 8.5% at 28 days.…”
Section: Fig 2 Water Absorption Capacity Of Samplementioning
confidence: 99%